Comparative analysis of activins A and B in the adult mouse epididymis and vas deferens. Issue 1 (January 2018) - Wijayarathna, Rukmali; de Kretser, David M; Sreenivasan, Rajini; Ludlow, Helen; Middendorff, Ralf; Meinhardt, Andreas; Loveland, Kate L; Hedger, Mark P
Abstract : Activin A regulates testicular and epididymal development, but the role of activin B in the epididymis and vas deferens is unknown. Mouse models with reduced activin A ( Inhba +/− and Inhba BK/+ ), or its complete absence ( Inhba BK/BK ), were investigated to identify specific roles of activins in the male reproductive tract. In 8-week-old Inhba +/− mice, serum activin A decreased by 70%, with a 50% reduction of gene expression and protein in the testis, epididymis and vas deferens. Activin B and the activin-binding protein, follistatin, were similar to wild-type. Testis weights were slightly reduced in Inhba +/− mice, but the epididymis and vas deferens were normal, while the mice were fertile. Activin A was decreased by 70% in the serum, testis, epididymis and vas deferens of Inhba BK/+ mice and was undetectable in Inhba BK/BK mice, but activin B and follistatin levels were similar to wild-type. In 6-week-old Inhba BK/BK mice, testis weights were 60% lower and epididymal weights were 50% lower than in either Inhba BK/+ or wild-type mice. The cauda epididymal epithelium showed infoldings and less intra-luminal sperm, similar to 3.5-week-old wild-type mice, but at 8 weeks, no structural differences in the testis or epididymis were noted between Inhba BK/BK and wild-type mice. Thus, Inhbb can compensate for Inhba in regulating epididymal morphology, although testis and epididymal maturation is delayed in mice lacking Inhba . Crucially, reduction or absence of activin A, at least in the presence of normal activin B levels, does not lead to major defects in the adult epididymis or vas deferens.